Productivity Enhancement in Engine Bearing Manufacturing Industry Through Integrated Work System and Job Design: the Ergonomic Perspective - Batish, Ajay Kumar (My University, 2006)
For long, the Indian industry remained protected from any international competition. The organizations were quite satisfied continuing with the old technology and working practices which were not very efficient. With the advent of globalization and liberalization and the whole world turning into a free market, many multinational companies entered the Indian market. These companies not only introduced advanced technology but also brought in world-class work practices and healthy work culture. The traditional Indian companies setup before liberalization have been left with no choice – either improve or perish. This has brought in a very welcome change. It is transforming the industry into more efficient and productive units. Higher levels of productivity, however, demand the employees to be in good physical and mental health, the working environment to be conducive to putting in hard and productive work, the work place design to be of the kind which helps in optimizing the output with minimum effort and fatigue. The subject of ergonomics has thus assumed a very important role in enhancing employee morale, his health, safety and productivity. Cut throat competition, advanced technology and newer techniques and methods of work has increased pressure in the workplace. The whole work culture is undergoing a transformation. Now almost every one in the organization is handling not a single job but a multitude of jobs. In addition, large product mix handled in any organization has also added to the variety of jobs being done by individuals. All this demands adapting to the new skills, techniques, technology and ways of work. It also demands planning, control and accomplishment of tasks in smaller lead times, lower costs, better quality and customer satisfaction. This transformation from traditional to highly demanding and taxing working dictates that there be a parallel change in the ergonomic requirements. There is, thus, a need to study and analyze the conditions existing from ergonomic point of view, and develop and design the job and the work environment needed in the prevailing and changing manufacturing scenario. Since no generalized or universal rules and designs can be developed for all the industries, the engine bearing manufacturing industry has been taken up for detailed study. The work has been carried out in three phases: Preliminary study of the engine bearing manufacturing organizations, detailed study of areas identified after the preliminary study, and synthesis and qualitative assessment of productivity gains and design of strategy for implementation of identified controls and validation in a phase-wise manner. .A preliminary study was carried out to identify the extent of change which has come in jobs carried out by the employees, the resultant change which should come in work system and job design, the status of ergonomics, and the areas needing further study and analysis. The areas identified after the preliminary study were (1) Work Postures, (2) Manual Material Handling Tasks, (3) Lifting Tasks, and (4) Job design and motivational aspects in a job. The detailed analysis of working postures has been carried out by observing workers on all the production lines of engine bearing manufacturing units and the ergonomic risks prevalent in there work postures which result in injuries/MSD’s and low productivity have been identified.. For analysis of work postures, Rapid Upper Limb Assessment (RULA) methodology has been employed. This is followed by identification of suitable provisions/ controls for implementation, as a direct outcome of the analysis. While assessing manual material handling tasks, contributing factors that have a direct bearing on the hazards associated with such tasks have been identified and grouped. For analyzing material handling tasks, the identified factors have been used to develop an assessment technique, MHAC (Material handling assessment chart) The manual material handling tasks, which had higher need and potential for improvement have been identified and detailed analysis of these tasks has been carried out using MHAC and improvements have been made/suggested. A survey of users of handling aids has been carried out to look at safety and usability, seeking opinions on the aids currently in use and on the factors, which most affect perceptions of their usability. The outcomes of the survey results have been used to design and fabricate a four-wheeled pallet trolley for use in the representative industry. The manual-lifting tasks at all stations during the manufacturing of engine bearings/ bushings have been evaluated using the revised NISOH Lifting Equation (1991). Wherever the assessment showed that, there is a possibility of risk of injury, modifications have been made/ suggested to eliminate or reduce the risk. Assessment of Job design has been carried out by using Job Diagnostic Survey (JDS) questionnaire (Hackman and Oldham, 1974). The study has been carried out on three job families: Production operators, Quality Staff & Inspectors, and Maintenance staff & Machine setting workers of engine bearing industry. Analysis of five measures of Motivating Potential as well as Measures of Growth Needs for the three job families has been carried out to find the number of employees in the ideal job-person match. The eight measures relating to the outcomes and satisfaction of a motivational situation have been analyzed jointly for all the operators taken together. After the analysis, the jobs needing re-design have been identified for each job family and using the cause and effect diagram and pareto technique, the root causes of problems relating to job design have been identified. Appropriate controls for the identified causes have been developed for each job family and gains in productivity and performance have been listed. The actual and expected results of various ergonomic provisions/controls implemented/suggested after the detailed analysis as described above have been summarized in terms of productivity and performance gains. The broad findings of the preliminary study, results of the analysis of work posture, material handling (both carrying and lifting tasks), job design and their impact on muscoloskeletal disorders (MSD’s) and productivity have been synthesized. The ergonomic provisions and controls implemented and suggested after the detailed analysis have been categorized into two broad categories, first where the extent of improvement in productivity is validated or calculated in quantitative terms and second, where the effect on productivity cannot be calculated precisely because it involves qualitative factors. For the second category, expert opinion has been utilized to quantify the expected gains. Productivity gains in all major areas of work postures, material handling tasks, lifting tasks and job design have been compiled from the details of implemented provisions and suggested provisions. For the purpose of synthesis and modeling for developing a strategy for implementation, the controls/ provisions identified have been grouped into broad generalized categories. The cost and productivity gains expected have then been listed for each of this generalized category of controls. Expert opinion has been utilized to identify factors and parameters affecting development of a generalized approach for implementation. The qualitative responses provided by experts to the specially designed questionnaire for the purpose has been converted to quantitative score and results have been listed in reducing order of their weighted scores. Generalization of various measures for developing an approach to be used by industry in future has been suggested using expert opinion. It has further been suggested that the implementation of the developed approach be carried out in three phases.
Keywords: Ergonomics; Productivity; Work Posture; Analysis; Material Handling; Job Design